Role of prenatal magnetic resonance imaging in fetuses with isolated severe ventriculomegaly at neurosonography: A multicenter study. (December 2021) - Di Mascio, Daniele; Khalil, Asma; Pilu, Gianluigi; Rizzo, Giuseppe; Caulo, Massimo; Liberati, Marco; Giancotti, Antonella; Lees, Christoph; Volpe, Paolo; Buca, Danilo; Oronzi, Ludovica; D'Amico, Alice; et al.
Abstract: Objective: The aim of this study was to report the rate of additional anomalies detected exclusively at prenatal magnetic resonance imaging (MRI) in fetuses with isolated severe ventriculomegaly undergoing neurosonography. Method: Multicenter, retrospective, cohort study involving 20 referral fetal medicine centers in Italy, United Kingdom, Spain and Denmark. Inclusion criteria were fetuses affected by isolated severe ventriculomegaly (≥15 mm), defined as ventriculomegaly with normal karyotype and no other additional central nervous system (CNS) and extra-CNS anomalies on ultrasound. In all cases, a multiplanar assessment of fetal brain as suggested by ISUOG guidelines on fetal neurosonography had been performed. The primary outcome was the rate of additional CNS anomalies detected exclusively at fetal MRI within two weeks from neurosonography. Subgroup analyses according to gestational age at MRI (<vs ≥ 24 weeks of gestation) and the laterality of ventriculomegaly (unilateral vs bilateral) were also performed. Univariate and multivariate logistic regression analysis was used to analyze the data. Results: 187 fetuses with a prenatal diagnosis of isolated severe ventriculomegaly on neurosonography were included in the analysis. Additional structural anomalies were detected exclusively at prenatal MRI in 18.1% of cases. When considering the type of anomaly, malformations of cortical development were detected on MRI in 32.4% cases, while midline or acquired (hypoxemic/hemorrhagic) lesions were detected in 26.5% and 14.7% of cases, respectively. There was no difference in the rate of additional anomalies when stratifying the analysis according to either gestational age at MRI or laterality of the lesion. At multivariate logistic regression analysis, the presence of additional anomalies only found at MRI was significantly higher in bilateral compared versus unilateral ventriculomegaly (OR: 4.37, 95% CI 1.21–15.76; p = 0.04), while neither maternal body mass index, age, severity of ventricular dilatation, interval between ultrasound and MRI, nor gestational age at MRI were associated with the likelihood of detecting associated anomalies at MRI. Conclusion: The rate of associated anomalies detected exclusively at prenatal MRI in fetuses with isolated severe ventriculomegaly is lower than previously reported, but higher compared to isolated mild and moderate ventriculomegaly. Fetal MRI should be considered as a part of the prenatal assessment of fetuses presenting with isolated severe ventriculomegaly at neurosonography.